The Serpent in the Garden of Weeden: A Comparison of Western Tiger Snake (Notechis scutatus occidentalis) Habitat Quality and Thermal Ecology in Native and Invasive Vegetation - Cornelis, Jari (Curtin University, 2021)
This thesis provides novel insights into the ecology and thermal biology of tiger snakes and their persistence in urban wetlands dominated by invasive plants. The similarities in prey availability, predation risk and physiological constraints of kikuyu-dominated wetlands compared to those retaining native vegetation permit the continued persistence of tiger snakes in these modified urban environments. Indeed, kikuyu grass provides for high-quality habitat, with abundant prey, low predation rates and favourable thermal conditions.